Increased Sylvian fissure angle as early sonographic sign of malformation of cortical development. (8th July 2019) - Pooh, R. K.; Machida, M.; Nakamura, T.; Uenishi, K.; Chiyo, H.; Itoh, K.; Yoshimatsu, J.; Ueda, H.; Ogo, K.; Chaemsaithong, P.; Poon, L. C.
ABSTRACT: Objective: To evaluate Sylvian fissure development by assessing Sylvian fissure angles in fetuses with malformation of cortical development (MCD). Methods: This was a retrospective study of 22 fetuses with MCD. Cases with a stored three‐dimensional (3D) brain volume acquired at 18 + 0 to 30 + 6 weeks of gestation at an ultrasound‐based research clinic between January 2010 and December 2017 were identified through a database. Of the 22 fetuses, seven had an extracranial abnormality, such as cardiac, renal, gastrointestinal and/or digital anomalies, and five had a minor abnormality such as micrognathia, low‐set ears and/or single umbilical artery. To confirm the final clinical diagnosis of brain abnormality, postmortem histological findings or prenatal or postnatal magnetic resonance images were used. For measurement of Sylvian fissure angle, an anterior coronal plane of the fetal brain on transvaginal 3D volume multiplanar imaging was visualized as a single image from the three orthogonal views. The right and left Sylvian fissure angles were measured between a horizontal reference line (0°) and a line drawn along the upper side of the respective Sylvian fissure. The Sylvian fissure angle on both sides was plotted on the graphs of the reference ranges for gestational age in weeks. Results: In 21 (95.5%; 95% CI, 86.8–100.0%) of 22 fetuses with MCD, the Sylvian fissure angle on one or both sides was larger than the 90 th percentile of the normal reference. There was one case with apparent focal MCD in the parietal lobe, but the Sylvian fissure angles were normal. A case with apparent unilateral cortical dysplasia and one with apparent unilateral schizencephaly had conspicuous discrepancies between the left and right Sylvian fissure angles. Abnormal genetic test results were obtained in six cases, including four cases with a mutation in a single gene. Conclusions: This study has shown that the Sylvian fissures, as defined by the Sylvian fissure angle, have delayed development in most MCD cases prior to the diagnosis of the condition. The Sylvian fissure angle may potentially be a strong indicator for the subsequent development of cortical malformation, before the time point at which the gyri and sulci become obvious on the fetal brain surface. Further research is required to validate these findings. © 2018 The Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of the International Society of Ultrasound in Obstetrics and Gynecology.